Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.17795/jjcdc-30234
|View full text |Cite
|
Sign up to set email alerts
|

Applying the Health Belief Model in Predicting Breast Cancer Screening Behavior of Women

Abstract: Background: Breast cancer is the most common cancer among Iranian women. However, early detection of this cancer leads to a timely treatment and better prognosis, which significantly improves the survival rate in patients. Objectives: The purpose of this study was to predict the breast cancer screening behavior of women who referred to health centers in Dezful, Iran, using the health belief model (HBM). Patients and Methods: This descriptive-analytical study was conducted on 226 women who were selected with cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 19 publications
1
13
1
Order By: Relevance
“…In addition, the results revealed that the participants with high perceived self-efficacy were 13.15 times more likely to perform BSE than those with lower perceived self-efficacy. The studies conducted in Iran by Masoudiyekta et al and Hasani et al indicated that perceived self-efficacy was the most powerful predictor of BSE [ 34 , 35 ]. Another study conducted in the United States also clarified that perceived self-efficacy was a predictor of performing BSEs among American women [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the results revealed that the participants with high perceived self-efficacy were 13.15 times more likely to perform BSE than those with lower perceived self-efficacy. The studies conducted in Iran by Masoudiyekta et al and Hasani et al indicated that perceived self-efficacy was the most powerful predictor of BSE [ 34 , 35 ]. Another study conducted in the United States also clarified that perceived self-efficacy was a predictor of performing BSEs among American women [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another quasi-experimental study based on the Health Belief Model was implemented in Iran to look at the effect of education on the behavior of breast cancer screening in women. The pre-and post-tests administered in the form of a researcher-made questionnaire three months before and after four teaching sessions showed remarkable improvements in knowledge, perceived severity, perceived benefits, perceived barriers, and cues to action (10). Both descriptive and experimental studies showed consistency in personal and environmental determinants.…”
Section: Personal Determinants and Environmental Factors From Descripmentioning
confidence: 92%
“…A combination of personal determinants such as low selfefficacy, low knowledge, high perceived barriers, and low perceived susceptibility; and environmental factors such as low awareness of physicians regarding the severity of metastatic breast cancer among refugee women, lack of health literate and culturally competent educational skills, and issues related to the local healthcare system (unavailability of funding for chronic disease screening and treatment for refugees, high costs of medical services, lack of properly educated nurses, and lack of transportation means from camps to hospitals) have been negatively affecting screening and chemotherapy completion rates among the target population (1,3,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Aside from the lack of funding allocated by the main refugee organization in the country, United Nations High Commissioner for Refugees (UNHCR), the absence of human right policies at the societal level to protect the integrity of refugees and ensure the equitable receival of urgent medical care by disadvantaged populations amidst prevailing political corruption has worsened mammography and treatment rates by contributing to the stigma associated with e refugee status in the host community (17,18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breast cancer is one of the most common cancers among women in both developed and developing countries. [ 1 ] It is the most common cancer in women aged 40–60 years and the second most common cancer in women aged 30–40 years, and it is also the second leading cause of cancer death in women (about 571 000 deaths) in the world. [ 2 3 ]…”
Section: Introductionmentioning
confidence: 99%